Establishing the correspondences between 2D UWB positions and image coordinates. Issue 1 (1st June 2022) - Zhang, Qiang; Li, Shiqian; Wei, Wei; Liu, Minchao; Wu, Shuang; Qin, Xue
Abstract: Ultra wide band (UWB) positioning system and camera are two types of sensors which records positions and images respectively. In many applications, it is expected to fuse the data obtained by the two types of sensors in two different coordinate systems. In this work, we study the problem of establishing the correspondences between 2D UWB positions and image coordinates of a camera. We propose a simple yet effective method which requires simple apparatus and does not need to know in advance the positions of the UWB anchors in camera frame. Experimental results have demonstrated the effectiveness of proposed method.